Histopathological analysis of placental lesions caused by Chlamydia abortus 1B vaccine strain in vaccinated ewes. Issue 5 (27th May 2022) - Caspe, Sergio Gastón; Livingstone, Morag; Wattegedera, Sean; Aitchison, Kevin; Underwood, Clare; Milne, Elspeth; Sargison, Neil; Chianini, Francesca; Palarea-Albaladejo, Javier; Longbottom, David
Abstract : Background: Chlamydia abortus is one of the most diagnosed causes of infectious abortion in small ruminants. Infections can be controlled using the live, attenuated C. abortus strain 1B vaccine, which has been associated with infection and abortion in animals. This study aimed to compare the severity and the distribution of lesions caused by this vaccine strain (vt) with those resulting from a wild-type (wt) infection. Methods: Two grossly affected and 1B-positive (by qPCR and RFLP analysis) placentas from a vaccinated sheep flock were analysed. Histopathological lesions and immunohistochemical labelling (IHC) were graded (increasing score from 0 to 5) according to their severity and distribution. Pathology in the vt infected placentas was compared with that in two wt infected placentas. Datasets generated for observed histological and pathological features were analysed using principal component analysis (PCA). Results: Histopathologically, the lesions in both vt and wt-placentas presented as typical multifocal necrosuppurative placentitis, associated with vasculitis, mural necrosis, and thrombosis. IHC for C. abortus revealed intense staining with a multifocal distribution in most cotyledons in both vt and wt placentas. Comparison of the pathological lesions between vt and wt by PCA revealed a similar distribution and severity, revealing a strong association with features such as necrosis and inflammatory infiltration between vt and wt placentas. A weaker association with IHC was observed. Conclusion: This study shows that the C. abortus attenuated 1B vaccine strain presents no significant differences in severity and distribution of pathological lesions from those typically observed following a wt infection.